Prediction of Unconfined Compression Strength for Saline-Alkaline Soils Mixed with Cement and Wheat Straw. (21st April 2020) - Xing, Guoqi; Liu, Changjiang; Xuan, Wei; Pan, Yueyue; Zhang, Bing; Zhao, Yue
Abstract : A series of unconfined compression tests were performed to investigate the influence of wheat straws on the unconfined compression strength for saline-alkaline soils and saline-alkaline soils mixed with cement. In unconfined compression tests, 20 groups of soil specimens were prepared at five different percentages of wheat straws content (i.e., 0.0%, 0.1%, 0.15%, 0.2%, and 0.25% by weight of saline-alkaline soils) and four different percentages of cement content (i.e., 0%, 3%, 6%, and 9% by weight of saline-alkaline soils), and unconfined compression tests were carried out after 3-, 7-, 14-, 28-, and 56-day curing periods. Test results indicated that the inclusion of wheat straws within saline-alkaline soils and saline-alkaline soils mixed with cement leads to an increase in the unconfined compressive strength of specimens and also changed the brittle behavior to a more ductile one for specimens. In addition, based on the results from unconfined compression tests, a formula for predicting the unconfined compression strength of specimens related to cement content, wheat straw content, curing periods, etc., was determined, and comparing with the results from unconfined compression tests, it had higher precision in predicting the unconfined compression strength of specimens.